JENIS, BENTUK, DAN MAKNA KALIMAT PERINTAH DALAM KISDAP “SATIPIS APAM BARABAI” KARYA IDA KOMALASARI - Eka Suryatin (Balai Bahasa Kalimatan Selatan, 2019)
This study discusses the types and forms of command sentences in the kangdap Banjar base kambang Banjar 'Satipis Apam Barabai' and the meaning of the command sentence in the Banjar kisdap kambang Banjar bases' Satipis Apam Barabai. 'Satipis Apam Barabai' and the meaning of the command sentence in the floating kisdap kangdap Banjar base 'Satipis Apam Barabai.' The research method uses descriptive qualitative methods with content analysis techniques. The data in this study are in the form of utterances containing command sentences contained in Kambang rampai kisdap basa Banjar “Satipis Apam Barabai” by Hj. Ida Komalasari. The data source in this study is Kambang rampai kisdap basa Banjar “Satipis Apam Barabai” by Hj. Ida Komalasari was published by the first printed Artikata publisher in December 2018 with a 112-page book thickness. The results showed the types of command sentences contained in the floating kisdap Banjar Satipis Apam Barabai bases there are four types, namely strict command sentences, ordinary command sentences, fine command sentences, and prohibited command sentences. The command sentence that is in the Banjar base kisdap ‘Satipis Apam Barabai’ means to rule, order, ask, and forbid.